Jewish and Christian Concepts of Time and Modern Anti-Judaism: Ousting the God of Time - Brearley, Margaret F. (Studies in church history, 1992)
One of the major factors which distinguish Judaism and Christianity from virtually all non-monotheistic religions is the concept of time. The Jews were alone among ancient peoples in worshipping the God of Time. In most ancient religions the pagan gods of space, embodied in sacred places and things, were worshipped. Nature was perceived pantheistically, as sacred, inhabited by spirits and devas. Gods of space were visualized in images: ‘Where there is no image, there is no god’, their worship necessarily involving idolatry. Generally anthropomorphic and often personifying man’s own instincts, such gods could inspire no clear moral code. Separation from them could be bridged only by physical means—by Dionysiac frenzy, by re-enactment of myths about them. Thus Cretans tore apart a living bull to re-enact Hera’s murder of Dionysos Zagreus; worshippers of Attis in Phrygia engaged in self-castration. Shamanisric trances, eating sacrifices, and temple prostitution were among other means of temporarily embodying the spatial gods.